2014
DOI: 10.1080/09168451.2014.877827
|View full text |Cite
|
Sign up to set email alerts
|

Targeted metabolomics for Aspergillus oryzae-mediated biotransformation of soybean isoflavones, showing variations in primary metabolites

Abstract: This study aimed to investigate the biotransformation of soybean isoflavones to hydroxyisoflavones, and the primary and secondary metabolite change during Aspergillus oryzae KACC40247-mediated fermentation by gas chromatography-time of flight-mass spectrometry and LC-MS with multivariate analysis. The mass spectrometric analysis revealed that acetylglycosides and glycosides decreased during the first 12 h of fermentation, while the aglycones increased up to that time point. This was followed by a decrease in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 35 publications
1
20
0
Order By: Relevance
“…Similar studies have also been carried out on the following interactions: Fusarium oxysporum –chickpea [84,85], Verticillium dahliae – Arabidopsis [86,87], Verticillium longisporum – Arabidopsis [88], Venturia inaequalis –apple [89], Alternaria solani –wild tomato [88], Alternaria brassicicola – Arabidopsis [90], Gymnosporangium asiaticum –Rosaceae plants [91], Cercospora beticola –sugar beet [92], Plectosphaerella cucumerina – Arabidopsis [93], Aspergillus oryzae –soybean [94], Penicillium digitatum –citrus [95], Zymoseptoria tritici –wheat [96], and Alternaria alternata –jujube fruit [97]. These studies have shown that metabolomics can be used to characterize plant-infecting fungal pathogens to identify some metabolites related to the resistance and to clarify plant resistance.…”
Section: Research Progress and Application Of Metabolomics In Fungmentioning
confidence: 99%
“…Similar studies have also been carried out on the following interactions: Fusarium oxysporum –chickpea [84,85], Verticillium dahliae – Arabidopsis [86,87], Verticillium longisporum – Arabidopsis [88], Venturia inaequalis –apple [89], Alternaria solani –wild tomato [88], Alternaria brassicicola – Arabidopsis [90], Gymnosporangium asiaticum –Rosaceae plants [91], Cercospora beticola –sugar beet [92], Plectosphaerella cucumerina – Arabidopsis [93], Aspergillus oryzae –soybean [94], Penicillium digitatum –citrus [95], Zymoseptoria tritici –wheat [96], and Alternaria alternata –jujube fruit [97]. These studies have shown that metabolomics can be used to characterize plant-infecting fungal pathogens to identify some metabolites related to the resistance and to clarify plant resistance.…”
Section: Research Progress and Application Of Metabolomics In Fungmentioning
confidence: 99%
“…In this study, total isoflavone content showed a gradual decrease with increase of time during fermentation and aging, however, aglycone content and its proportion were increased until 3 or 6 months of aging, and then slowly decreased until 12 months of aging. High β-glucosidase activity of Aspergillus oryzae and Bacillus licheniformis , used in this study, was reported [ 54 55 ]. In this study, it was observed that not only β-glucoside isoflavone but also malonyglucoside and acetylglucoside contents were decreased by fermentation, thereby, the accumulated aglycone content increased by fermentation and aging, however, it reached the maximum level at 3 months of aging and then decreased slowly.…”
Section: Discussionmentioning
confidence: 99%
“…Probable reason might be due to biotransformation of aglycones into hydroxyisoflavones, such as 8-hydroxydaidzein, hydroxygenistein, and hydroxyglycitein [ 53 ]. Lee et al [ 55 ] recently reported that fermentation of a solution of ground steamed soybeans with Aspergillus oryzae at 30℃ decreased acetylglycoside and glycoside content and aglycone content increased after the first 12 hours of fermentation, however, aglycone content was decreased after the second or third 12 hours of fermentation due to the conversion to hydroxyisoflavone, and the content of this substance showed strong correlation with antioxidant activity.…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of providing a global view of metabolism and characterization by its silent phenotype, we used metabolomics which is an independent part of systems biology [14]. Today, it has been applied to many field of studies in microorganisms [15], plants [16], environmental [17], and mammalian systems [18]. The powerful UPLC-Q-TOF-MS and GC-TOF-MS analytical platforms are often used in plant metabolomics to profile differential metabolites.…”
Section: Introductionmentioning
confidence: 99%